Doing Academia Differently: Creative Reading/Writing-With Posthuman Philosophers. (June 2022) - Bozalek, Vivienne Grace
This article considers how academic practices such as reading and writing might be reconfigured as creative processes through thinking-with posthuman philosophies and theorists, particularly, but not confined to the works of Karen Barad and Erin Manning. Both Erin Manning and Karen Barad are involved with creative philosophies and practices, albeit from different vantage points. Manning's work engages with arts-based practices such as research-creation through process philosophies, whereas Barad reads queer theory through quantum physics to develop their agential realist framework and diffractive methodology. Although Manning and Barad never refer to each other's work, this article proposes that thinking-with both of these feminist philosophers might be fruitful to consider how reading and writing as part of research projects and graduate supervision might be enacted creatively and differently.